2017
DOI: 10.1037/sgd0000202
|View full text |Cite
|
Sign up to set email alerts
|

Outness, concealment, and authenticity: Associations with LGB individuals’ psychological distress and well-being.

Abstract: Outness, concealment, and authenticity have all been theorized to be important to lesbian, gay, and bisexual (LGB) well-being and psychological outcomes. Using a sample of 373 LGB participants, the current study tests the unique contributions of each of these constructs to outcomes measuring psychological well-being, depressive symptoms, and perceived stress. Hierarchical regressions revealed that increased outness was a significant predictor of increased depressive symptoms (counter to the hypothesis but cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(156 citation statements)
references
References 32 publications
9
142
2
3
Order By: Relevance
“…LGBT populations based on identity concealment (Riggle, Rostosky, Black, & Rosenkrantz, 2017). Public policy approaches such as antidiscrimination laws will be required to reduce the negative influences of social stigma on the mental health of Thai LGBT populations.…”
Section: Most Thaimentioning
confidence: 99%
“…LGBT populations based on identity concealment (Riggle, Rostosky, Black, & Rosenkrantz, 2017). Public policy approaches such as antidiscrimination laws will be required to reduce the negative influences of social stigma on the mental health of Thai LGBT populations.…”
Section: Most Thaimentioning
confidence: 99%
“…A few researchers have examined associations between perceived stress and the other variables of the present study. Riggle et al, (2017) found that outness and perceived stress were negatively correlated, but that outness did not significantly predict perceived stress, demonstrating the role of potential third variables in their association. The authors noted that perceived stress is an indicator of general stress, while outness might be predictive of stress that is specific to queer people.…”
Section: Perceived Stress As a Mental Health Variablementioning
confidence: 87%
“…In response, the gay athlete can either remain silent or disclose his identity and risk facing rejection. Weighing the risks and benefits of identity disclosure is a unique and recurring burden for queer individuals in a heterosexist world (Riggle, Rostosky, Black, & Rosenkrantz, 2017). Furthermore, the implications and results of coming out vary on a case by case basis.…”
Section: Heterosexismmentioning
confidence: 99%
See 2 more Smart Citations